Shop Smart, Stay Safe: Marketplace Safety Education for Students at SMP Negeri 8 Jakarta - Vita Briliana; Wasisto Ruswidiono; Deasy Ariyanti Rahayuningsih (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The dominance of the younger generation correlates with high exposure of adolescents to the digital ecosystem (social media and e-commerce), which is saturated with promotions, influencers, and hidden advertisements. This increases the risk of impulsive purchases, fraud, and exposure to online lending/pay later services without adequate understanding. The community service program